Evaluating Hand Properties of High Counts and High Density Fabrics (Journal of Fiber Bioengineering and Informatics, 2014)
Fabric hand is defined as the human tactile sensory response towards fabric, which involves not onlyphysical but also physiological, perceptional and social factors. Fabric hand is one of the most importantcharacteristic of a fabric. This paper discusses the relationship between technical features of high countsand high density fabrics and their hand evaluation. 13 samples of high counts and high density fabricswere selected to be measured by the Kawabata Evaluation System (KES). The range of the mechanicalproperties of high counts and high density fabrics was given. Using factor analysis with quartimaxrotation, 5 factors model was generated. The relationship between the 5 factors and the technicalfeatures was shown by using correlation analysis. The study in this paper can offer references for thequality control of high counts and high density fabric design.
Keywords: Fabric Hand Evaluation; KES; Factor Analysis; High Counts and High Density Fabrics